Family Planning: Legal Regulations And Practice in Slovenia - Pinter, Bojana; Vogrin, Veronika (Medicine, Law & Society, 2025)
Family planning allows individuals to achieve their desired number of children, and to control the timing of their pregnancies. This can be accomplished through contraception, with reducing the need for abortion, and infertility treatments. Pregnancy and childbirth are related to maternal mortality, which can be reduced with the prevention of unintended pregnancies. Access to contraception and safe abortion is crucial. At the 1968 International Conference on Human Rights in Teheran, family planning was declared a basic human right. In 1974, Yugoslavia was the first country in the world declaring the constitutional right to freedom of choice in childbearing. The safety of artificial pregnancy termination has been greatly enhanced by the improvements of vacuum aspiration technique, developed by Slovenian doctors in 1964. In Slovenia, abortion rates are constantly decreasing since 1980 due to available contraception and established contraceptive service. The history of family planning in Slovenia and actual situation are presented.